Unpacking how teacher support enhances learning engagement in physical education: A serial mediation model of academic self-efficacy and task orientation among Chinese college students - Xinjian Xu; Yongneng Tan; Borhannudin bin Abdullah (PLoS ONE, 2025)
Background Despite the Chinese government’s focus on student physical education, low student participation in physical activities persists, necessitating efforts to improve engagement. Purpose This study explores the relationship between teacher support and university students’ engagement in physical education, focusing on the mediating roles of academic self-efficacy and sport task orientation, Methods A quantitative analysis was conducted to investigate the mediation effects among 2,625 students from various regions and school types. Results The study demonstrated significant correlations between teacher support, academic self-efficacy, sport task orientation, and PELE. Teacher support was found to positively influence physical education learning engagement (PELE) both directly and through academic self-efficacy and sport task orientation. The model fit indices suggested a good fit, Conclusion The findings highlight the critical roles of teacher support, academic self-efficacy, and sport task orientation in enhancing students’ engagement in physical education, offering valuable insights for improving physical education practices.